New genera and new species of Western Australian cicadas (Hemiptera: Cicadidae) - Moulds, Max; Marshall, David C. (Zootaxa, 2022)
The cicada fauna of Western Australia is briefly reviewed. Six genera and 14 species are recorded from the State for the first time bringing the total of known species and subspecies to 105 and a list of all 105 is provided. Among the taxa here recorded are five new genera and 13 new species belonging to the tribes Macrotristriini (Illyria viridis sp. n.), Pictilini (Chrysocicada trophis sp. n.), and Cicadettini (Calipsalta gen. n., Calipsalta brunnea sp. n., C. fumosa sp. n., C. viridans sp. n., Kalarko gen. n., Kalarko ferruginosus sp. n., Ewartia adusta sp. n., Parvopsalta gen. n., Parvopsalta victoriae sp. n., Pedana gen. n., Pedana hesperia sp. n., Pegapsaltria gen. n., Pegapsaltria lutea sp. n., Pyropsalta amnica sp. n., Py. patula sp. n., and Py. rhythmica sp. n). In addition, Erempsalta hermannsburgensis (Distant, 1907) is redescribed and its presence in Western Australia (and four other States) documented for the first time. Songs are analysed for all species except two species of Pyropsalta where recordings were unavailable.